2015
DOI: 10.17696/2318-3691.22.2.2015.142
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento Dos Cirurgiões Dentistas Em Relação Ao Câncer De Boca

Abstract: ResumoIntrodução: Diante dos baixos índices de cura e sobrevida do câncer bucal, é crucial que se diagnostique essa doença precocemente. Objetivo: Avaliar o grau de conhecimento de cirurgiões dentistas a respeito do câncer bucal. Casuística e Métodos: A pesquisa foi realizada por meio da aplicação de um questionário a um grupo de cirurgiões dentistas, exercendo atividades clínicas no município de Fernandópolis, SP, Brasil. Resultados: De 124 questionários distribuídos, o índice de resposta à pesquisa foi de 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
0
9
0
8
Order By: Relevance
“…Several studies have reported lacks on dental surgeons' knowledge regarding oral cancer, and although some studies described this knowledge as satisfactory, the need for improving dental surgeons' knowledge and capacities for adequately diagnosing and educate general population regarding oral self-examination and oral cancer prevention is still undisputed. [12][13][14] Although high oral cancer occurrence rates reported in literature, during oral cancer prevention campaign performed in Fernandópolis, SP, Brazil in 2015 we identified an extremely low rate of oral cancer diagnosis (0.13%). However, we believe this low oral cancer diagnosis rate might not be attributed to a decrease in oral cancer prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported lacks on dental surgeons' knowledge regarding oral cancer, and although some studies described this knowledge as satisfactory, the need for improving dental surgeons' knowledge and capacities for adequately diagnosing and educate general population regarding oral self-examination and oral cancer prevention is still undisputed. [12][13][14] Although high oral cancer occurrence rates reported in literature, during oral cancer prevention campaign performed in Fernandópolis, SP, Brazil in 2015 we identified an extremely low rate of oral cancer diagnosis (0.13%). However, we believe this low oral cancer diagnosis rate might not be attributed to a decrease in oral cancer prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,11 Furthermore, several studies have demonstrated lacks on dental surgeons' knowledge and capacity for clinically recognizing and early diagnosing OSCC, and although some studies have demonstrated satisfactory knowledge regarding this disease by these professionals, there is a general agreement regarding the need for continuous education programs aiming to adequately train dental surgeons for early diagnosing and preventing OSCC. [12][13][14] Aiming to raise awareness regarding oral cancer among general population, Fernandópolis city (São Paulo, Brazil) public health service and the Camilo Castelo Branco University Dentistry School, performed an oral cancer prevention campaign, which in patients were clinically examined by public health dental surgeons searching for oral cancer clinically suggestive signals, and furthermore, dental surgeons instructed patients regarding the importance of early diagnosing oral cancer, oral self-examination and prevention attitudes regarding this malignance. During this campaign, several oral lesions were diagnosed among these patients; therefore, the aim of this paper is to present diagnosed lesions rates from this campaign.…”
Section: Introductionmentioning
confidence: 99%
“…O diagnóstico precoce do câncer de boca é fundamental para um prognóstico favorável da doença, uma vez que o atraso nesse diagnóstico resulta em aumento da morbidade enfrentada pelo paciente e diminui as chances de cura e sobrevida. É importante que o CD possa identificar os sinais e sintomas iniciais da doença e tenha condutas adequadas diante de cada caso, o que não é possível sem um conhecimento satisfatório sobre o tema 17 .…”
Section: Discussionunclassified
“…Several studies have been performed aiming to evaluate the capacity of dentists to detect oral cancer and educate general population about the risk factors for oral cancer development and the importance of oral self-examination and early diagnosis of oral cancer, and although in some studies dentists have demonstrated satisfactory knowledge regarding oral cancer, some lacks on this knowledge have been reported [4,27] and furthermore, there is a general agreement regarding the need for continued education programs for these professionals aiming to improve their capacities on adequately diagnosing and preventing oral cancer [10,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosing OSCC is challenging due, basically, to two factors; affected patients usually take long times to appear for professional evaluation, most commonly appearing for treatment four to eight months after noticing any alteration on oral mucosa [6,20,26]. Another challenging fact is that dentists, who keeps close contact with patients' oral cavity, are not always properly qualified in recognizing possible malignant oral lesions neither oral potentially malignant lesions and adequately conduct a right diagnosis, referring for oncological treatment, or, in oral potentially malignant disorders cases, conduct the patient through adequate clinical follow-up [7,11,27].…”
Section: Introductionmentioning
confidence: 99%